Surveillance strategies for the detection of disease outbreaks in the Pacific islands: meta‐analysis of published literature, 2010–2019. Issue 8 (11th June 2020) - Craig, Adam T.; Kaldor, John; Schierhout, Gill; Rosewell, Alexander E.
Abstract: Objective: Due to their tropical location, development status and the limited capacity of health systems, Pacific island counties and territories are particularly susceptible to infectious disease outbreaks; but evidence as to the optimal way in which outbreaks are detected is scarce. In this review, we synthesise evidence from literature about how outbreaks are detected in Pacific island countries and territories and critique factors identified as inhibiting surveillance practice. Method: For this systematic review, we searched electronic databases Embase, Global Health, MEDLINE and MEDLINE Epub from 1 January 2010 and 31 March 2019 for reports describing infectious disease outbreaks occurring in the Pacific islands. Reports were included if they reported the method by which an outbreak was detected or the time between an outbreak's onset and its detection. We extracted information about the report type and authors, the outbreak and its method/s of detection, and pertinent issues inhibiting surveillance practice. Results: Of 860 articles identified, 37 reports describing 39 outbreaks met the inclusion criteria. Most outbreaks ( n  = 30) were identified through formal event‐based surveillance; six through syndromic surveillance; and two by ad hoc notification from the community. Barriers to early outbreak detection included population isolation; lack of resources and infrastructure to support surveillance implementation and signal investigation; and broader health system factors such as preparedness planning and availability of laboratory services. Conclusion: Most surveillance‐related gain in the Pacific islands may be made through building formal event‐based surveillance systems and streamlining reporting processes to facilitate outbreak notification. This observation is pertinent given the focus on establishing and expanding syndromic surveillance approaches for outbreak detection in the islands over the last decade. Abstract : Objectif: En raison de leur situation tropicale, de leur état de développement et de la capacité limitée des systèmes de santé, les comtés et territoires des îles du Pacifique sont particulièrement sensibles aux épidémies de maladies infectieuses, mais les données quant à la manière optimale de détecter les épidémies sont rares. Dans cette étude, nous synthétisons les données de la littérature sur la manière dont les épidémies sont détectées dans les pays et territoires des îles du Pacifique et les facteurs critiques identifiés comme entravant la pratique de la surveillance. Méthode: Pour cette analyse systématique, nous avons recherché dans les bases de données électroniques Embase, Global Health, MEDLINE et MEDLINE Epub du 1 er janvier 2010 et du 31 mars 2019 pour des rapports décrivant les épidémies de maladies infectieuses survenant dans les îles du Pacifique. Les rapports ont été inclus s'ils indiquaient la méthode de détection d'une épidémie ou le délai entre le début d'une épidémie et sa détection. Nous avons extrait les informations sur le type de rapport et les auteurs, l'épidémie et sa ou ses méthodes de détection, ainsi que les problèmes pertinents qui entravent la pratique de la surveillance. Résultats: Sur les 860 articles identifiés, 37 rapports décrivant 39 ménages ont satisfait aux critères d'inclusion. La plupart des épidémies ( n  = 30) ont été identifiés suite à une surveillance formelle basée sur les événements, six suite à une surveillance syndromique et deux suite à une notification ad‐hoc de la communauté. Les obstacles à la détection précoce des épidémies comprennent l'isolement de la population, le manque de ressources et d'infrastructures pour soutenir la mise en œuvre de la surveillance et l'investigation des signaux, ainsi que des facteurs plus généraux du système de santé tels que la planification de la préparation et la disponibilité des services de laboratoire. Conclusion: La plupart des gains liés à la surveillance dans les îles du Pacifique peuvent être réalisés par la mise en place de systèmes de surveillance formels basés sur les événements et l'aiguillage des processus de report pour faciliter la notification des épidémies. Cette observation est pertinente étant donné l'accent mis sur l'établissement et l'expansion des approches de surveillance syndromique pour la détection des épidémies dans les îles au cours de la dernière décennie.